Indonesia's responsibility towards Rohingya refugees: analysis of the 1951 Refugee Convention - Gunawan, Yordan; Novendra, Carissa Shifa; Febrila, Aldha (Faculty of Law, University of Muhammadiyah Malang, 2024)
The Acehnese people refused the boat carrying more than 200 Rohingya migrants in early 2024; therefore, UNHCR is pleading with the Indonesian authorities to allow them to disembark. The UNHCR report states that there are currently 1,608 Aceh refugees, including 140 survivors from the previous year. People are increasingly worried about the impact of the significant influx of Rohingya individuals in Aceh. Indonesia's acceptance of those seeking safety for humanitarian reasons has significantly affected the Acehnese population. Indonesia is being pressured to provide assistance to Rohingya refugees despite not being a signatory to the Refugee Convention. The issue at hand is whether Indonesia is legally obligated to help Rohingya refugees under the Refugee Convention. This study utilized normative legal research, commonly known as document analysis involving a qualitative examination of secondary data sources. The investigation included sources such as books, papers, and treaties, specifically focusing on the Refugee Convention of 1951. Indonesia, as it is not a signatory to the Refugee Convention, does not have a legal duty to aid the Rohingya refugees in Aceh based on the Refugee Convention. This study employed normative legal research, analyzing documents qualitatively with secondary sources like books, articles, and treaties, notably the 1951 Refugee Convention. Consequently, since Indonesia has not ratified the Refugee Convention, it is not bound by legal obligations to assist the Rohingya refugees in Aceh. However, Indonesia still maintains a responsibility according to the Universal Declaration of Human Rights.